RASIO KEPEMILIKAN DAN RASIO EFISIENSI TERHADAP PROFITABILITAS DAMPAKNYA PADA NILAI PERUSAHAAN - Ulfa Ika Putri; Azhar Affandi (Faculty of Economic and Business, University of Pasundan, 2018)
This study aims to determine the condition of ownership ratio proxyed by equity, the efficiency ratio proxyed by BOPO, profitability ratios proxied with Return On Asset, and company value and to find out how much influence of variable ownership and efficiency to profitability impact on firm value at 18 banking companies listed on the BEI period 2008-2015. This research uses descriptive and verificative methods. Data analysis methods used are multiple regression, multiple correlation, and coefficient of determination. The results showed that the ratio of ownership and efficiency ratio simultaneously and partially have significant effect on profitability. The dominant variable is the ownership ratio. Profitability has a significant effect on corporate value.